Establishment of a plant regeneration system from callus of Dendrobium cv. Serdang Beauty - Khosravi, Alireza; Abdul Kadir, Mihdzar; Kazemin, S. B.; Qamaruz Zaman, Faridah; De Silva, Angela Ee (Academic Journals, 2008)
An in vitro propagation protocol was established for the Dendrobium Serdang Beauty orchid. The propagation protocol utilized calli tissues that were successfully initiated from protocorm-like bodies (PLBs) explants, while the leaf and root tip explants died. The percentage of protocorm-like bodies explants responding to calli formation was 100% in all tested levels of IAA, IBA and NAA auxin treatments. The highest amount of calli (49.59 gram) proliferated on MS medium containing 1.5 mg/L IBA. These calli successfully regenerated on media supplemented with either KIN or BAP cytokinins and combined treatments of KIN and IAA (4 mg/L) or NAA (1.5 mg/L). However, media supplemented with only 1 mg/L KIN was sufficient to produce significantly high percentage of plantlet formation (80%), high number of planlets per explant (4-5 plantlets) and high mean fresh weight per plantlet (11.128 g). These plantlets were acclimatized on all tested media and obtained satisfactory rate of plantlet survival (80-100%), mean number of leaves per plant (4-6 leaves), and mean leaf length (4 - 5 cm). Among these media, charcoal was considered the most economical and available material in the local market. During the development of this protocol, substantial necrosis of calli were observed when cultures were treated with 2,4-D and BAP. It was proposed that the presence of ethylene within the cultures, which is known to be emitted by plant growth regulators into the micro-climate of in vitro culture vessels, is the determining factor of a suitable plant growth regulator for the survival and growth of the Dendrobium Serdang Beauty calli cultures in our study.